1982
DOI: 10.1126/science.6800032
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Chlorine-Containing Antibiotic From the Freshwater Cyanobacterium Scytonema hofmanni

Abstract: Scytonema hofmanni, a filamentous freshwater cyanobacterium (blue-green alga), produces secondary metabolites which inhibit the growth of other cyanobacteria and green algae. A rapid, qualitative assay for this inhibition has been developed with Synechococcus as the test organism. This assay procedure has led to the isolation and characterization of an antibiotic (named cyanobacterin) from Scytonema. The antibiotic has a molecular weight of 430 and an empirical formula of C23H23O6Cl and contains a gamma-lacton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
0
3

Year Published

1986
1986
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(71 citation statements)
references
References 13 publications
0
66
0
3
Order By: Relevance
“…Cyanobacterin, an algicide from 50'tollema "oJmalllli, also inhibits PS I1 (Mason et al 1982, Gleason andPaulson 1984), but unlike nschereJ1in contains an atom of chlorine and has a higher molecular weight (Pignatello et al 1983). Other biogenic algicides that inhibit photosynthesis have been isolated from Pandorina l1lorum (Patterson et al 1979) and Chal'll (Wium-Andersen et al 1982).…”
Section: Fismentioning
confidence: 99%
“…Cyanobacterin, an algicide from 50'tollema "oJmalllli, also inhibits PS I1 (Mason et al 1982, Gleason andPaulson 1984), but unlike nschereJ1in contains an atom of chlorine and has a higher molecular weight (Pignatello et al 1983). Other biogenic algicides that inhibit photosynthesis have been isolated from Pandorina l1lorum (Patterson et al 1979) and Chal'll (Wium-Andersen et al 1982).…”
Section: Fismentioning
confidence: 99%
“…Microalgae are much more amenable to this type of study, and to immobilization, and in this respect show greater potential for industrial development. There are, in particular, very few reports of antibacterial activity from freshwater microalgae (Debro & Ward, 1979;Mason et al, 1982). As part of our programme of screening microalgae for novel compounds of potential medicinal value, we have therefore screened 400 freshwater algae, both eucaryotes and cyanobacteria, for the presence of antibacterial activity.…”
mentioning
confidence: 99%
“…Thus, cyanobacterin is believed to be an allelopathic compound which enables S. hofmanni to compete with more prolific cyanobacterial species. Initial studies with cyanobacterin suggested that it acted as a general membrane disruptor (9). However, growth assays using highly purified cyanobacterin clearly indicated that the compound is active against both cyanobacteria and eukaryotic algae, but does not inhibit the growth of nonphotosynthetic microorganisms (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…The cyanobacterium (blue-green alga), Scytonema hofmanni (formerly UTEX2 1581, now UTEX 2349) was found to inhibit the growth of other algae in two species cultures (9). Inhibition was due to production and excretion of a secondary metabolite by S. hofmanni.…”
mentioning
confidence: 99%